Genetically engineered biomimetic ATP-responsive nanozyme for the treatment of cardiac fibrosis - Xueli Zhao; Yuze Qin; Bowen Li; Yue Wang; Jiao Liu; Bo Wang; Jia Zhao; Jiaqi Yin; Lanlan Zhang; Jing Li; Junzhe Huang; Kun Chen; et al. (Journal of Nanobiotechnology)
Abstract Background Cardiac fibrosis plays a critical role in the progression of various forms of heart disease, significantly increasing the risk of sudden cardiac death. However, currently, there are no therapeutic strategies available to prevent the onset of cardiac fibrosis. Methods and results Here, biomimetic ATP-responsive nanozymes based on genetically engineered cell membranes are adapted to specifically recognize activated cardiac fibroblasts (CFs) for the treatment of cardiac fibrosis. By fusing the anti-FAP CAR genetically engineered cell membrane to zeolitic imidazole frameworks-90 (zif-90) cores loaded with antioxidant nanozymes CeO2 and siCTGF (siRNA targeting CTGF), these nanoparticles, called FM@zif-90/Ce/siR NPs, are demonstrated to effectively reduce the accumulation of myofibroblasts and the formation of fibrotic tissue, while restoring cardiac function. Conclusions These findings demonstrate that the combination of CeO2 and siCTGF has a beneficial curative effect on cardiac fibrosis, with significant translational potential.